Evaluation of cyclosporine-sparing effects of polyunsaturated fatty acids in the treatment of canine atopic dermatitis. (April 2016) - Müller, M.R.; Linek, M.; Löwenstein, C.; Röthig, A.; Doucette, K.; Thorstensen, K.; Mueller, R.S.
Highlights: Oral fatty acid supplementation led to a significant decrease in cyclosporine dose in atopic dogs. Pruritus was better controlled with concurrent oral fatty acids in atopic dogs on cyclosporine. Adverse events on this combination therapy were mild and predominantly gastrointestinal. Abstract: A randomised, double-blinded, placebo-controlled multicentre trial was conducted in 36 dogs with atopic dermatitis to evaluate the cyclosporine-sparing effect of polyunsaturated fatty acids. Dogs were stable on their individual cyclosporine dosage and received either a mainly omega-3 fatty acid product with a minor omega-6 fatty acid fraction or placebo, orally for 12 weeks. Dogs were examined every 4 weeks and the Canine Atopic Dermatitis Extent and Severity Index (CADESI-03) was determined by a clinician. Pruritus, quality of life, global condition and coat quality were scored by the owner. If the dog's CADESI-03 and/or pruritus score improved by at least 25% compared with the previous visit, the cyclosporine dosage was decreased by approximately 25%. If the scores deteriorated by at least 25%, the cyclosporine dosage was increased by the same percentage. The median daily cyclosporine dosage/kg bodyweight decreased in the active group from 4.1 mg to 2.6 mg and in the placebo group from 3.5 mg to 3.3 mg over the study period. The difference between the two groups was significant ( P  = 0.009). The improvement in median pruritus score from inclusion to completion was significantly greater in the active group than in the placebo group ( P  = 0.04). There was no significant difference in CADESI-03 changes between groups ( P  = 0.38). The results of this study indicate a cyclosporine-sparing effect of a mainly omega-3 fatty acid supplement in dogs with atopic dermatitis.